Unexpected clinical sequelae of Gitelman syndrome: hypertension in adulthood is common and females have higher potassium requirements - Berry, Miriam R. (Oxford University Press, 2013)
BACKGROUND: Gitelman syndrome (GS) is a rare inherited disorder caused by mutations in SLC12A3, encoding the thiazide-sensitive transporter NCCT (sodium chloride co-transporter) in the distal tubule. It is characterized by renal potassium (K) and magnesium (Mg) wasting, relative hypotension and hypocalciuria. However, there is phenotypic variability and long-term studies are scarce. METHODS: We retrospectively assessed clinical and genetic characteristics, and electrolyte requirements, in a cohort of 36 patients with genetically proven GS. RESULTS: The 21 males and 15 females were of median age 39.5 years, range 17–66 years. Six were diagnosed in childhood. Among the 72 mutant alleles, 41 different sequence alterations were identified, of which 13 were previously unreported. Surprisingly, 44% (n = 16) of the cohort has developed hypertension (13 males, 3 females, P = 0.019; median age 53 versus 57 years, P = 0.95). One was already hypertensive by age 23 years. Currently normotensive patients were significantly younger: median 37 versus 55 years (P = 0.005). Hypertensive patients were more likely to harbour mutations in the C-terminal half of the NCCT protein (P = 0.016). Females required more K (median 128 versus 72 mmol/day; P = 0.01) but not Mg. Those with exon 26 and/or at least one destructive mutation had higher K requirements than those with neither: 108 versus 72 mmol (P = 0.016) and a tendency towards higher Mg needs: 30 versus 7.4 mmol (P = 0.07). CONCLUSIONS: Our findings suggest that the development of secondary hypertension may be an expected feature of the ageing GS population despite the obligate salt wasting that characterizes the disorder. We hypothesize that this may be related to chronic secondary hyperaldosteronism. The apparently more severe phenotype in women may be related to the effects of female sex hormones on expression or function of NCCT.